The Analysis of Transitional Justice Initiatives and The Flaw of Prosecution on The Past Human Rights Violation in Indonesia (Tanjung Priok Case) - Saibih, Junaedi; Danil, Elwi; Warman, Kurnia; Mulyati, Nani (UI Scholars Hub, 2023)
The political transition from the New Order era to Reform Era has initiated questions to the transitional government about transitional justice initiatives. This chapter discusses the theoretical perspectives on transitional justice that have been developed by many scholars in their publications. Besides the theoretical perspectives about transitional justice, this chapter also discusses transitional justice elements, the forms, and the institution of justice in transitional regimes. The discussion in this chapter is important as a measurement of the transitional government initiatives to reach political stability and reconciling with the past. The explanation about the forms and the element of justice then be discussed comprehensively in part about the government initiatives, in addition to reconciling with the past violation and creating “Victims-Centred Transitional Justice”. This study specifically raises aspiration or expectation from the victims on the transitional justice policy made by the transitional government. The room for victims to speaks their version comparing to many versions on the incident will be narrated in the specific part on the incidents (Tanjung Priok Incident 1984) as well as reminiscing the victims’ experiences with the violations of human rights when the incident occurred. After discussing the incident, then next part shall narrate about the government policy in settling past severe violation of human rights and the effort of victim’s supporters in the House of Representatives before promulgating the Law on Human Rights Court. The later part is very important to be discussed in formulating a conclusion to half-hearted transitional justice in Indonesia.